A survey on E-payment systems: elements, adoption, architecture, challenges and security concepts - Masihuddin, Muddassir; Khan, Burhan Ul Islam; Mattoo, M. Mueen Ul Islam; Olanrewaju, Rashidah Funke (Indian Society for Education and Environment & Informatics Publishing Limited, 2017)
This paper is aimed at investigating and increasing awareness about various concepts related to Electronic Payment Systems (EPS) including its advantages, challenges and security considerations. The proposed study also evaluates the adoption of e-payment systems and the resulting impact on economy of a nation. Methods/Statistical Analysis: In this paper, a comprehensive survey on all the aspects of electronic payment was conducted after analysis of several research studies on online payment systems. The most recent references and information have been explored in order to gain significant information about electronic payments systems. Findings: From the study conducted, it can be elucidated that despite various issues that usage of electronic payment systems pose, these are identified as a positive step towards the economic development of a nation. Nevertheless, its full potential can be realized only by raising its awareness among people. Applications/Improvements: With the advancement in technology and popularity of Internet, the perception of making online transactions is bound to gain momentum. In the future, the payment modes currently